(untitled) (Research, Society and Development, 2020)
Actinic cheilitis (AC) is a oral disorder potentially malignant with dysplastic proliferations of keratinocytes. The lesion has a predilection for the red zone of the lower lip and may be closely related to excessive exposure to sunlight. The aim of this study was to report a clinical case of AC in a cardiac patient, admitted to the intensive care unit. Male patient, leucoderma, 82 years old, with a whitish lesion on the red zone of the lower lip, pedicled and sessile areas, well-marked limits and irregular shape. The incisional biopsy was performed in the intensive care unit bed and sent to the laboratory of pathological analysis in the State of Paraíba (LACEN). Microscopy showed an epidermis thickened by acanthosis, with cells showing nuclear pleomophism and hyperchromism. In the dermis, the presence of vascular ectasia, diffuse lymphocytic infiltrate and basophilic degeneration of elastic fibers, areas with foci of superficial erosion of the lining epithelium covered by a crust of necrotic and fibrinoleucocytic material were also observed. The anatomopathological diagnosis was ulcerated actinic cheilitis. The treatment performed was total surgical excision with monitoring of the healing process until the patient’s hospital discharge. It was concluded that the treatment proposed to the patient was decisive. Also the presence of the dentist in a hospital environment facilitated the access and treatment of a oral disorder potentially malignant, favoring the prognosis of the case.